A Novel Surgical Technique for Percutaneous Fixation of Scaphoid Fractures with Sniper Technique : A Case Report - Chusing, Natdanai (Srinagarind Medical Journal, 2023)
Background and Objects: The operative treatment of a nondisplaced or minimally displaced scaphoid waist fracture can be performed using dorsal percutaneous fixation. This article presents a novel surgical technique for dorsal percutaneous fixation of scaphoid fractures. It is designed for individuals with limited procedural experience and aims to offer a more straightforward alternative to the widely used Slade technique, known for its complexity. Method: The authors provide a detailed description of the procedure for dorsal percutaneous fixation surgery using headless screws. The operation was performed on a patient who had a scaphoid waist fracture. Result: Postoperatively, the effective compression length measured 9.5 mm, and an angle of 78.6° to the fracture. Bone union was achieved 8 weeks after the surgery. Conclusion: This novel surgical technique can be an alternative to dorsal percutaneous fixation surgery for scaphoid waist fractures.